Dynamic variation in second language acquisition : a language processing perspective - Dyson, Bronwen Patricia (Processability approaches to language acquisition research & teaching, 2021)
"Dynamic Variation in Second Language Acquisition makes a cutting-edge contribution to knowledge about how second language learners develop their second language. Drawing comprehensively on Processability Theory's theoretical understanding that individual variation dynamically interacts with ordered stages of language acquisition, the book provides an informative, critical analysis of historical and contemporary debates about the role of variation in linguistic variation, particularly second language variation. Richly illustrated with a forensic year-long study of how eight adolescent learners of English vary in their acquisition of syntax and morphology, this monograph shows that learners vary in their timing of development between two distinct learner types along a continuum and without skipping stages. The book uncovers how learner variation is dynamic and quite (although not entirely) systematic and how this variation contributes to change in the second language. It will be essential reading for researchers, students, and practitioners"--